P390 The impact of anti-TNF therapy in adjuvant setting on postoperative recurrence patterns over decades in complicated Crohn's disease. (25th January 2019) - Colombo, F; Frontali, A; Conti, L; Baldi, C; Ardizzone, S; Maconi, G; Corsi, F; Foschi, D; Sampietro, G M
Abstract: Background: Surgical resection of diseased bowel in complicated Crohn's disease (CD) is frequently not curative and post-operative recurrence remains a significant problem in a large amount of patients. The aim of the study was to evaluate the impact of anti-TNF therapy in the prevention of CD patients' surgical recurrence in a Tertiary Italian IBD Center over decades. Methods: The Prospective Sacco Database for Surgery of CD (ProSaDS-CD) was retrospectively reviewed to analyse primary (Pr) and re-operative (Re) characteristics of patients operated on in the two decades 1994–2004 (Pr1–Re1) and 2005–2015 (Pr2–Re2). Gender, age, location, behaviour, smoking habit, perianal disease (PCD), time to surgery, indication for surgery, number and length of intestinal locations, number of resection and strictureplasty (SP), postoperative adjuvant therapy, and 25 years surgical recurrence were analysed using the chi-square test, Fisher exact test, Student's t -test, Kaplan–Meier time-to-event estimates, and log-rank test where appropriate. Results: From the ProSaDS-CD, 807 primary and 154 recurrent patients were divided in Group-Pr1 ( n = 337), Group-Pr2 ( n = 470), Group-Re1 (111), and Group-Re2 (43). Group-Pr2 patients have more frequent diagnosis at A1 and A3 ages ( p = 001), same Location ( p = 0.5) and Behaviour ( p = 0.74), longer disease duration ( p = 0.001), less smoking habit ( p = 0.0007), more intestinal locations ( p = 0.0001) and extension ( p = 0.0001), more anti-TNF-α adjuvant therapy ( p < 0.0001), and lower long-term surgical recurrence ( p = 0.0001). Overall surgical recurrence at 10 and 20 years was 20% and 32%. At 10 years, Group-Re1 and Group-Re2 have 30% and 12% recurrence, respectively ( p = 0.0001). At time of recurrence, Group-Re2 patients have more penetrating indication to surgery ( p = 0.05), more SP procedures ( p = 0.002), more small bowel locations ( p = 0.007) and extension ( p = 0.02), and less smoking habit ( p = 0.04). Period 1 (Pr1) vs. period 2 (Pr2) postop 25 years recurrence. Conclusions: In the last decade, surgery for CD has increased in paediatric patients and in the elderly, with a more aggressive pattern in terms of number and extension of locations, and penetrating complications. Strictureplasties in recurrent patients may reduce further intestinal damage. Anti-TNF-α adjuvant treatment and stop smoking seems to significantly change the course of recurrent disease.